Heart Failure - Alexander, Lori (MD Conference Express, 2007)
Approximately 0.4–2% of the European population has heart failure (HF), representing more than 14 million people. Another 4–5 million people in the United States are affected. The prognosis for older patients with HF is similar to that for severe malignant diseases, with a median survival of less than 5 years [Thomas et al. Heart Fail Clin 2007]. This article discusses definitions and classification, pharmacologic therapies, prognostic factors, and patient education.